2005
DOI: 10.1210/jc.2004-2474
|View full text |Cite
|
Sign up to set email alerts
|

CHARGE Syndrome Includes Hypogonadotropic Hypogonadism and Abnormal Olfactory Bulb Development

Abstract: These findings suggest that CHARGE syndrome includes the main features of Kallmann syndrome, which is defined by hypogonadotropic hypogonadism combined with a defective sense of smell and abnormal olfactory bulb development. This forebrain abnormality, if confirmed in a larger group of patients, could serve as a major new criterion for the diagnosis of CHARGE syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 38 publications
7
131
1
3
Order By: Relevance
“…New diagnostic criteria have been proposed in the past few years (see reference 41 ). Moreover, it has been reported that most if not all CHARGE patients have both olfactory bulb aplasia or hypoplasia and HH, 42,43 that is, the two KS defining features. Consequently, previously reported KS cases associated with congenital heart disease 44 or choanal atresia 45 could in fact represent unrecognised mild CHARGE cases.…”
Section: Differential Diagnosis: Normosmic Idiopathic Hh and Charge Smentioning
confidence: 99%
“…New diagnostic criteria have been proposed in the past few years (see reference 41 ). Moreover, it has been reported that most if not all CHARGE patients have both olfactory bulb aplasia or hypoplasia and HH, 42,43 that is, the two KS defining features. Consequently, previously reported KS cases associated with congenital heart disease 44 or choanal atresia 45 could in fact represent unrecognised mild CHARGE cases.…”
Section: Differential Diagnosis: Normosmic Idiopathic Hh and Charge Smentioning
confidence: 99%
“…The guidelines we present here for cranial imaging in patients with CHARGE syndrome are based on previously published neuro‐radiologic recommendations (Asakura et al, 2008; Bergman, Janssen, et al, 2011b; Fujita et al, 2009; Gregory et al, 2013; Pinto et al, 2005; Vesseur, Free, et al, 2016a) in addition to current insights in detectable neuro‐radiologic abnormalities and anatomic variants in patients with CHARGE syndrome (see Table 3). …”
Section: Overview Of Guidelines and Recommendations From Literaturementioning
confidence: 99%
“…Olfactory deficits are commonly accompanied by hypoplasia or aplasia of the olfactory bulbs in the brain [55,[60][61][62]. It was discovered, through electrophysiological and behavioral assays, that Chd7 heterozygous mice display complete anosmia, lack of odor discrimination, and olfactory bulb hypoplasia [61,63].…”
Section: Chd Proteins In Human Diseasementioning
confidence: 99%